KUALITAS SUMBER DAYA MANUSIA DALAM MENYELESAIKAN BERKAS TAGIHAN DI SEKRETARIAT DAERAH KABUPATEN MINAHASA UTARA BAGIAN UMUM - TIRZA WINOWODA; FEMMY TULUSAN (JURNAL ADMINISTRASI PUBLIK, 2022)
The problem with human resources actually lies in the skills or abilities that exist in aperson. Most civil servants do not master their own work which shows a poor work ethic, besidesthat they cannot make their own decisions, and lack self-discipline. This directly shows theirquality as private employees who are paid by the community and the state, but are of poor quality.If the office recruits characters like this, the result will only lead to inefficiencies, complicatedproblems, and decreased productivity. This study aims to find out how the Quality of HumanResources is in Completing Billing Files at the Regional Secretariat of the General Section. Themethod used is a qualitative approach. By type of case study. The use of this method is to exploredata as detailed as possible until the data obtained is saturated. This study used in-depthinterviews, observation and documentation from the field for data collection methods. Thisresearch found that civil servants understand their respective job parts through the training theyattended, besides that experience during education is also useful in completing billing files. evenso there are still obstacles that arise such as system and network errors and then the completenessof documents and the accuracy of documents often hinders the process of completing billing files.Interestingly, this study found something new from the determination and seriousness of civilservants, namely that employees often work overtime until midnight to complete bills that arehampered due to existing constraints. This research provides input in the future to continueresearch with the theme of Quality of Human Resources. This study suggests the RegionalSecretariat of North Minahasa Regency to involve more civil servants in technical guidance sothat the knowledge gained can increase the productivity of completing invoices.Keyword: Quality of Human Resoources, PNS, Technical Guidance, Invoice File, Productivity